Overcrowding‐mediated stress alters cell proliferation in key neuroendocrine areas during larval development in Rhinella arenarum. Issue 2 (28th January 2016) - Distler, Mijal J.; Jungblut, Lucas D.; Ceballos, Nora R.; Paz, Dante A.; Pozzi, Andrea G.
ABSTRACT: Exposure to adverse environmental conditions can elicit a stress response, which results in an increase in endogenous corticosterone levels. In early life stages, it has been thoroughly demonstrated that amphibian larval growth and development is altered as a consequence of chronic stress by interfering with the metamorphic process, however, the underlying mechanisms involved have only been partially disentangled. We examined the effect of intraspecific competition on corticosterone levels during larval development of the toad Rhinella arenarum and its ultimate effects on cell proliferation in particular brain areas as well as the pituitary gland. While overcrowding altered the number of proliferating cells in the pituitary gland, hypothalamus, and third ventricle of the brain, no differences were observed in areas which are less associated with neuroendocrine processes, such as the first ventricle of the brain. Apoptosis was increased in hypothalamic regions but not in the pituitary. With regards to pituitary cell populations, thyrotrophs but not somatoatrophs and corticotrophs showed a decrease in the cell number in overcrowded larvae. Our study shows that alterations in growth and development, produced by stress, results from an imbalance in the neuroendocrine systems implicated in orchestrating the timing of metamorphosis. J. Exp. Zool. 9999A:XX–XX, 2016. © 2016 Wiley Periodicals, Inc.